Cultural critique and avant-garde theatre in post-socialist China: Meng Jinghui's 'I love therefore I am'. (March 2015) - He, Donghui
The literal translation of avant-garde from French is 'foreguard'. While the front has been diversely defined in various permutations of the movement, the cutting edge of avant-garde theatre in China and many post-socialist countries is largely retrospective and anti-futuristic. This is particularly true for the campus-based fringe theatre of the early 1990s, which is regarded as the highlight of avant-garde theatre in China. An alternative venue spearheaded by young theatre artists, avant-garde fringe theatre is notable for unpacking the cultural and political constructs of the Chinese socialist period as it played out through the artists' own formative experiences. Directed by Meng Jinghu, I Love XXX chronicles the moral emotions that are central to a generation's self-identity. The play, which is composed of more than 700 parallel sentences prefixed with 'I love', presents a meticulously constructed emotional archive of the generation that was born in the late socialist period and came of age in post-socialist China. Imitating rites of passage and classroom drills, the play effectively illuminates the impact affective education had on an individual's self-perception. The fact that the play was revived in 2013 – 19 years after its initial appearance – proves its enduring relevance in contemporary China.